PERILAKU KONSUMSI SANTRI PONDOK PESANTREN DARUSSALAM SENGKUBANG DITINJAUDALAM PERSPEKTIF RELIGIUSITAS - Budi Gunawan (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
Currently, more and more students or Islamic boarding school students are buying educational goods not because of their utility value, but because they are influenced by lifestyle, for an image that is directed and formed by the way of thinking of students or Islamic boarding school students who have been influenced by advertisements and models on television, infotainment shows, fashion magazines, celebrity lifestyles, environmental factors and various other forms of popular culture. The description of the consumption behavior of students at the Darussalam Sengkubang Mempawah Islamic Boarding School is interesting to study because in their teens, students at the Darussalam Sengkubang Mempawah Islamic Boarding School are often found to spend their money excessively not because of necessity. The approach used in this study is a qualitative approach, by trying to construct reality and understand something hidden behind the phenomena that have appeared on the surface. The results of the study show that the consumption behavior of students at the Darussalam Sengkubang Islamic Boarding School can be seen from spending on daily needs and ownership of clothes and others. The factors behind students' consumptive behavior are external factors including reference groups and the surrounding environment. While the internal factors of the institution are following friends and pride in appearance. In terms of daily needs, they prioritize fulfilling the desire to buy snacks and food outside the Islamic Boarding School that are more varied without any limits on spending their pocket money. While in terms of clothing, they have clothes that exceed the capacity of the wardrobe provided at the Islamic Boarding School because there are no limits on clothing ownership. So that in the end, consumer behavior or israf appears.